Спектр биологической активности произ-водных пиразоло[1,5-а]пиримидина и пути их модификации (обзор) - Данагулян, Г. Г.; Гарибян, В. К. («Գիտություն» հրատ.)
Обзор посвящен обсуждению литературных данных и собственных результатов исследований, касающихся синтеза и биологической активности (в частности, противоопухолевой, антимикробной, противогрибковой, противовирусной, противовоспалительной, противосудорожной и др.) пиразоло[1,5-a]пиримидинов. Приводятся схемы и способы синтеза различных производных, содержащих заместители в как в пиразольном, так и в пиримидиновом кольцах, а также их влияние на отдельные рецепторы и биологическую активность. В обзоре приводятся некоторые данные об органических красителях и иных веществах пиразоло[1,5-a]пиримидинового ряда, которые исследованы в качестве средств визуализации опухолей. Ակնարկը նվիրված է պիրազոլո[1,5-а]պիրիմիդինների սինթեզին և կենսաբանական ակտիվությանը վերաբերող գրական տվյալների և սեփական արդյունքների քննարկմանը, մասնավորապես դրանց հակաուռուցքային, հակամանրէային, հակասնկային, հակավիրուսային, հակաբորբոքային, հակացնցումային հատկություններին: Բերվում են պիրազոլային և պիրիմիդինային օղակներում տարբեր տեղակալիչներ պարունակող բազմաթիվ ածանցյալների բանաձևեր և սինթեզի եղանակներ, ինչպես նաև դրանց կենսաբանական ակտիվությունը և ազդեցությունը ռեցեպտորների վրա: Ակնարկում ներկայացված են նաև որոշ տվյալներ պիրազոլո[1,5-а]պիրիմիդինային շարքին վերաբերող օրգանական ներկանյութերի և այլ միացությունների մասին, որոնք փորձարկվել են որպես քաղցկեղը տեսաբացահայտող գործիքներ: The review is dedicated to discussing the literature data and our own research results regarding the synthesis and biological activity (in particular, antitumor, antimicrobial, antifungal, antiviral, anti-inflammatory, anticonvulsant, etc.) of pyrazolo[1,5- a]pyrimidines. Schemes and methods for the synthesis of various derivatives containing substituents in both the pyrazole and pyrimidine rings are presented, as well as their effect on individual receptors and biological activity. The review provides insights into the study of organic dyes and other substances of the pyrazolo[1,5-a]pyrimidine series, which have been studied as tumor imaging agents. The review presents an original method for the preparation of polysubstituted pyrazolo[1,5-a]pyrimidines by recycling 2-alkylpyrimidinium salts. The reaction of 4,6-dimethylpyrimidinyl-2-acetic acid ethyl ester iodomethylate with carboxylic acid hydrazides leads to the formation of pyrazolo[1,5-a]pyrimidines. In this transformation, the triatomic fragment C-N-N of the hydrazide is included in the pyrazolopyrimidine molecule, and the nitrogen atom of the N-alkyl group is eliminated from the pyrimidine ring.
Keywords: Органическая химия; Биоорганическая химия